A Theory of the Nominal Term Structure of Interest Rates - Constantinides, George M. (Review of Financial Studies, 1992)
A model of the nominal term structure of interest rates is developed that has a positive and stationary process for the interest rate and delivers closed-form expressions for the prices of discount bonds and European options on bonds. Unlike the one-state-variable version of the Cox, Ingersoll, and Ross (1985) model, this model—even in its one-state-variable version—allows the term premium to change sign as a function of the state and the term to maturity, and also allows for shapes of the yield curve that are observed in the U.S. data but that are disallowed in the Cox, Ingersoll, and Ross model